2016
DOI: 10.1105/tpc.16.00016
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Stress Regimes Affect the Circadian Clock and Cause Jasmonic Acid-Dependent Cell Death in Cytokinin-Deficient Arabidopsis Plants

Abstract: ORCID IDs: 0000-0002-9888-7003 (I.F.); 0000-0002-6299-347X (M.R.)The circadian clock helps plants measure daylength and adapt to changes in the day-night rhythm. We found that changes in the light-dark regime triggered stress responses, eventually leading to cell death, in leaves of Arabidopsis thaliana plants with reduced cytokinin levels or defective cytokinin signaling. Prolonged light treatment followed by a dark period induced stress and cell death marker genes while reducing photosynthetic efficiency. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(144 citation statements)
references
References 153 publications
(174 reference statements)
7
137
0
Order By: Relevance
“…JA and its derivatives such as methyl jasmonate (MeJA) are reported to be involved in various plant biological activities including cell division, fruit growth and ripening (Creelman and Mullet, 1997). It also plays an important role in plant adaptation during abiotic stresses (Clarke et al, 2009; Yoon et al, 2009; Brossa et al, 2011; Nitschke et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…JA and its derivatives such as methyl jasmonate (MeJA) are reported to be involved in various plant biological activities including cell division, fruit growth and ripening (Creelman and Mullet, 1997). It also plays an important role in plant adaptation during abiotic stresses (Clarke et al, 2009; Yoon et al, 2009; Brossa et al, 2011; Nitschke et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythm is a fundamental biological system in humans, animals and plants that regulates various physiological functions such as sleep–wake cycle, energy metabolism, cell division, post-transcriptional regulation (Koike et al, 2012; Cardinal-Aucoin and Steel, 2016; Lopez-Minguez et al, 2016; McAlpine and Swirski, 2016; Nitschke et al, 2016), and endocrine system (Gachon et al, 2004; Lowrey and Takahashi, 2004). The master circadian clock, located in the suprachiasmatic nucleus (SCN), is an essential activator of downstream molecular events critical to the generation of circadian rhythms (Dunlap, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to LD‐dependent lesion formation in cat2 (Chaouch et al, ), ozone‐triggered lesions in Arabidopsis are more easily induced by equal‐time exposure in LD compared with SD (Dghim et al, ). Such effects may be related to circadian clock rhythms, which have been reported to interact with oxidative stress and related phytohormone signalling (Nitschke et al, ). Here, by using a short‐term exposure to oxidative stress of intracellular origin, we have shown that gene expression responses in leaves are strongly dependent on the history of the plant, and that this cannot be explained by day length‐dependent differences in CAT3 expression.…”
Section: Discussionmentioning
confidence: 99%